The application of the chromometric sample method in the aspect of hyphodradic behavior - Viznyuk, Inna (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
In the article, through the prism of competence tasks, the features of forming the professional readiness of future specialists to self-realization in conditions of hypochondriac nosology with psychosomatic trait are considered. Exploring this issue, we can emphasize the important point that in order to achieve professional success, a person must be endowed with individual professionally significant qualities characteristic of the chosen profession, which in the long-term activity change the psyche of the individual and can cause hypochondrial disorders with psychosomatic manifestation. Focusing on the confirmation or refutation of the hypothesis, we examined the relationship of psychosomatic manifestations of hypochondriacal character with the localization of their manifestations within a certain chronotype. In the course of the research there was a need to specify the interrelation of professional requirements and personal potentials that contribute to preserving the psychosomatic health of a person and promoting self-development in professional activity. Specialists of different professions also have features that distinguish them from each other, but in this case, it is the preservation of psychosomatic health of these people and is an urgent problem, which will solve the harmonious development, psychosomatic state of personality, psycho-functional state in the implementation of their own creative search and professional treasure. In the aspect of educational-informative problems, the criterion-effective component of the model, which includes motivational-value, cognitive- personal, creative-activity, reflexive-regulatory criteria of increasing the level of readiness of future specialists for psycho-emotional safety of activity, has been determined. Given such basic emotional attitudes in the human body, we can say that situational anxiety is the trigger mechanism in the pathogenesis of psychosomatic manifestations of hypochondriacally character, namely hypochondriacal behavior with disturbance of the skin. Intrusive conditions include: avoiding contact with objects that serve as a source of germs and bacteria; obsession with purity and the like. Fear and feelings of inferiority, social isolation, negativity accompanied by frustration, irritability, frustration, guilt, suspicion, anger were also observed in other indicators of the conducted research. It is established that the above criteria contributed to the isolation of psychological and temporal indicators of hypochondriacal diseases, which act as a methodological basis for the development and practical implementation of the system of chronological and psychological prediction of the course of hypochondria, outline specific directions of medical and psychological disorders On the basis of this problem we have developed an algorithm for chronobiological prognosis of psychosymptomatic symptoms, course, treatment efficiency and optimization of adaptive capacity of patients with hypochondrial disorders. Its essence was to acquaint the study participants with information about the recurrence of hypochondrial disorders, the causes of their recurrence and the consequences in the educational and information environment.